"Europeization or ""Russianization""? Dilemmas over Reforming the Philippines Political System / uropeizacja czy ""rosjanizacja""? Dylematy związane z reformą systemu politycznego na Filipinach" - Czech, Franciszek (Europeizacja czy ""rosjanizacja""? Dylematy związane z reformą systemu politycznego na Filipinach", 2010)
The article focuses on one of the most crucial political discourses in the Philippines. Since the 1987 Constitution was enacted in grate haste after collapse of Marcos' regime, there has been an ongoing debate on fundamental reshape of the political system. The article considers Philippines struggles with the redefinition of the central figure in that system - the President. It presents political context of the constitutional debate in a historical perspective. Moreover, it indicates the most important arguments of adherents and opponents of the constitutional change. It focuses on the constitutional position of the president and his relations with other major political actors
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 357-366
Keywords: the Philippines; constitution; debate; political system